Lepus timidus Linnaeus 1758 - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
59. Mountain Hare Lepus timidus French: Liévre variable / German: Schneehase / Spanish: Liebre de montana Other common names: Blue Hare, Snow Hare, Eurasian Arctic Hare, Varying Hare, White Hare; Irish Hare (hibernicus), Alpine Mountain Hare (varronis) Taxonomy. Lepus timidus Linnaeus, 1758, “in Europa.” Formerly, the three arctic species, L. timidus, L. arcticus, and L. othus, were included in L. timidus based on morphological characteristics that, relative to their distributions, form a circumpolar “ring species.” This is also supported by genetic analysis of mtDNA, although evidence based only on mtDNA should be treated cautiously. There is also the view that two species exist: L. timidus in the Old World and L. arcticus in Greenland, northern Canada, Alaska, and the Chukchi Peninsula, Russia. Other lagomorph taxonomists consider that L. arcticus is conspecific with L. timidus and distinct from L. othus. Until conclusive evidenceis available, the three species are considered to be distinct with L. timidus in the Old World, L. othus in Alaska, and L. arcticus in northern Canada and Greenland. Nevertheless, the border between L. timidus and L. othusis not clear and might be either in the Bering Strait or in the Kolyma region, Russia. Recent molecular phylogenetic study suggests that the break occursin the Bering Strait, but more studies are required for a conclusive demarcation because the study was only based on mtDNA. Six populations of L. timidus are geographically separated and morphologically distinct and therefore can be treated as subspecies (abe, ainu, hibernicus, orii, scoticus, and varronis). Because division into subspecies is mostly based on pelage characteristics, it must be considered preliminary. Three studies analyzing geographic variation of metric characters of the skull of L. timidus demonstrated clinal variations. This doubts the advisability of identifying subspecies in L. timidus. Origin of subspecies of L. timidus in Europe from a panmictic population during the Weichsel period is ...